2021
DOI: 10.1097/ccm.0000000000004845
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biomarkers to Identify Acute Kidney Injury to Help Detect Sepsis in Patients With Infection

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
(14 reference statements)
0
8
1
1
Order By: Relevance
“…[14][15][16][17] Given the impact sepsis-associated AKI has on morbidity and mortality, 3 prevention is imperative. The first step to successfully prevent AKI is an 19,20 Building on this, the implementation of protective measures may provide a way to improve outcomes, even if previous research has indicated that the pathophysiology of septic AKI may differ in parts from AKI induced by other causes. 21 The assumption that standard AKI prevention measures, like hemodynamic optimization and goaldirected therapy approaches to fluid resuscitation, may be insufficient in preventing sepsis-associated AKI has been fueled by null results regarding AKI incidence in major trials of early goal-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Given the impact sepsis-associated AKI has on morbidity and mortality, 3 prevention is imperative. The first step to successfully prevent AKI is an 19,20 Building on this, the implementation of protective measures may provide a way to improve outcomes, even if previous research has indicated that the pathophysiology of septic AKI may differ in parts from AKI induced by other causes. 21 The assumption that standard AKI prevention measures, like hemodynamic optimization and goaldirected therapy approaches to fluid resuscitation, may be insufficient in preventing sepsis-associated AKI has been fueled by null results regarding AKI incidence in major trials of early goal-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of sepsis-related organ dysfunction is characterized by dysregulated host responses, including inflammation and immunosuppression (2). The kidney is one of the most vulnerable organs in sepsis, with acute kidney injury (AKI) occurring in more than 50% of patients (3). Early identification is key to providing supportive care and limiting further insult (4).…”
Section: Introductionmentioning
confidence: 99%
“…Point-of-care C-reactive protein, procalcitonin, or lactate levels have also been proposed to help potentially identify those patients with infection at risk of progressing to sepsis in the community setting, although the benefit of such testing in nonhospitalized patients warrants further study (17,(22)(23)(24). Urinary biomarkers may hold promise in detecting organ injury from sepsis, as the urinary product of tissue inhibitor of metalloproteinase-2 × insulin-like growth factor binding protein 7 (NephroCheck Astute Medical, Inc., San Diego, CA) may help detect sepsis-related kidney injury in patients with infection (but not meeting sepsis criteria) nearly 1 day prior to traditional criteria of serum creatinine and urine output being met (25). Additional point-of-care technologies are also in development for molecular and immune-based diagnostics (26).…”
Section: Discussionmentioning
confidence: 99%